Manufacturing 2002
DOI: 10.1115/imece2002-39117
|View full text |Cite
|
Sign up to set email alerts
|

A Frequency Domain Force Model With Shearing and Ploughing Mechanisms for a Generalized Helical End Mill

Abstract: For a generalized helical end mill, this paper presents a frequency domain force model considering the ploughing as well as the shearing mechanisms. The differential chip load and the corresponding cutting forces are first formulated through differential geometry for a general helical cutting edge. The differential cutting force is assumed to be a linear function of the chip load with a proportional shearing force and a constant ploughing force. The total milling force in the angle domain is subsequently compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Earlier works on the establishment of the dualmechanism cutting constants have been based on the orthogonal cutting test data [7]; this test data is then transformed to the cutting constants for a ball end cutter according to its cutting edge geometry. Based on the analytical milling force model, recent works have shown that these cutting constants can be conveniently identified from the average forces of two cutting tests in [8,9] and estimated online from the forces of a single cutting test for a cylindrical end mill in [10] and for a ball end mill in [11]. This online identification of cutting constants make possible the real-time monitoring of the milling process by making available to the user the detailed information about both the shearing and the ploughing processes.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Earlier works on the establishment of the dualmechanism cutting constants have been based on the orthogonal cutting test data [7]; this test data is then transformed to the cutting constants for a ball end cutter according to its cutting edge geometry. Based on the analytical milling force model, recent works have shown that these cutting constants can be conveniently identified from the average forces of two cutting tests in [8,9] and estimated online from the forces of a single cutting test for a cylindrical end mill in [10] and for a ball end mill in [11]. This online identification of cutting constants make possible the real-time monitoring of the milling process by making available to the user the detailed information about both the shearing and the ploughing processes.…”
Section: Introductionmentioning
confidence: 99%
“…Under this coordinate arrangement, the total milling forces for an N-flute general helical end mill in the angle domain have been presented by Wang and Zheng [9] as a Fourier series expression with Fig. 1 The cutting geometry and parameters in a general cutting configuration for a general helical end mill…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations